Ganesha and Parvati figures outside the door - Temples of India Project Team (Jio Institute, 2024)
Two separate devakostha niches are present. The larger one houses Ganesha, while the smaller one houses Parvati. Ganesha is depicted dancing and four-armed holding a goad, a vessel of sweets, etc. Parvati is standing erect in sambhanga with a jata-mukuta. She is depicted with six arms, holding a trident, akshayamala, spear, etc. These devakoshthas are affixed on a late structure on Harsha Hill.